Adipose tissue-derived stromal vascular fraction for treating hands of patients with systemic sclerosis: a multicentre randomized trial Autologous AD-SVF versus placebo in systemic sclerosis. (23rd July 2021) - Daumas, Aurélie; Magalon, Jérémy; Jouve, Elisabeth; Casanova, Dominique; Philandrianos, Cécile; Abellan Lopez, Maxime; Mallet, Stéphanie; Veran, Julie; Auquit-Auckbur, Isabelle; Farge, Dominique; Levesque, Hervé; Benhamou, Ygal; et al.
Abstract: Objective: To assess the superiority of adipose tissue-derived stromal vascular fraction ( AD-SVF) injection into the fingers vs placebo in reducing hand disability in systemic sclerosis (SSc) patients. Methods: We performed a double-blind, multicentre, phase II trial from October 2015 to January 2018 in France. SSc patients with a Cochin Hand Function Scale (CHFS) ≥20/90 were randomized 1:1 to receive injection of AD-SVF or placebo. AD-SVF was obtained using the automated processing Celution 800/CRS system. The placebo was lactated Ringer's solution. The primary efficacy end point was the change of the CHFS score from baseline to 3 months. Secondary efficacy endpoints included the CHFS score at 6 months, hand function, vasculopathy, hand pain, skin fibrosis, sensitivity of the finger pulps, Scleroderma Health Assessment Questionnaire, patients and physician satisfaction, and safety. Results: Forty patients were randomized. The AD-SVF and placebo groups were comparable for age, sex ratio, disease duration, skin fibrosis of the hands and main cause of hand disability. After 3 months' follow-up, hand function significantly improved in both groups with no between-group difference of CHFS (mean change of −9.2 [12.2] in the AD-SVF group vs −7.6 [13.2] in the placebo group). At 6 months, hand function improved in both groups. Conclusion: This study showed an improvement of hand function in both groups over time, with no superiority of the AD-SVF. Considering the limits of this trial, studies on a larger population of patients with homogeneous phenotype and hand handicap should be encouraged to accurately assess the benefit of AD-SVF therapy. Trial registration: ClinicalTrials.gov, https://clinicaltrials.gov, NCT02558543. Registered on September 24, 2015.